COVID-19 as a Catalyst for Digital Payment Growth: A Case Study of Mehsana City - Chhaya Patel; Dr. Rita Sharma; Prof. (Dr.) Ashish B. Joshi; Dr. M. Samir Gopalan (Revista Electronica de Veterinaria, 2025)
This case study investigates the impact of the COVID-19 pandemic on the adoption and growth of digital payment systems in Mehsana City, Gujarat, India. The research employs a mixed-methods approach, combining quantitative data analysis of digital transaction volumes and qualitative insights from local businesses and consumers. Findings indicate a significant acceleration in digital payment adoption, with a 150% increase in digital transactions during the first six months of the pandemic. The study highlights the role of social distancing measures, government initiatives, and changing consumer preferences in driving this shift. It concludes that while COVID-19 acted as a catalyst, the growth in digital payments is likely to have long-lasting effects on Mehsana's economic landscape.